A hybrid MADM approach for the evaluation of different material handling issues in flexible manufacturing systems - Sandhya Dixit; Tilak Raj (Administrative Sciences, 2018)
In today's versatile and dynamic industrial scenario more and more industries are adopting advanced manufacturing technologies and systems like flexible manufacturing system (FMS) which combines the efficiency of a mass production line and the flexibility of a job shop. Material handling equipment form an important component of FMS and using proper material handling equipment can enhance the production process, provide effective utilization of manpower, increase production and improve system flexibility. In this research the main material handling issues in a FMS are identified and further evaluated using ISM and TOPSIS approaches. The purpose of identification of these issues and their analysis is to allow researchers and practicing managers to pay proper attention to these issues which may help them in designing the material handling systems in their organisations in a better way.
Keywords: 350; manufacturing; FMS; material handling equipment; MADM; ISM; TOPSIS